Real-time Transactions Fraud Detection Via Machine Learning Techniques : A Review - Tripathi, Kapil Dev; Rajput, Vikas Singh (International Journal of Computer Sciences and Engineering, 2020)
This paper represents survey of various techniques utilized in Credit Card Fraud Detection (CCFD) mechanisms. There are many new and modern techniques depending upon Neural Network (NN) and Artificial Intelligence (AI), Data mining (DM), Artificial Immune System (AIS), Bayesian Network (BN), Fuzzy Logic Based System, Decision Tree (DT), K- nearest neighbor (KNN) algorithm, Support Vector Machine (SVM), Machine Learning (ML), Genetic Programming (GP) etc., which has developed fraudulent transactions to detect various credit card. Various techniques for the FD system have been explained. The powerful FD system, which detects the fraud, but also detects it in a precise manner, is needed in order to stop these frauds. They also need to make our systems learn about or adapt to future new methods of fraud from past frauds. The concept of CC fraud, or its different types, has been introduced in this paper.